Reign the earth: the elementae - Gaughen, A.C. (New york , Bloomsbury, 2018)
"Having sacrificed her freedom to establish peace with a neighboring kingdom, Shalia discovers that she has the power to control Earth the day she marries Calix, whose only motivation is to eliminate the Elementae"
O level
Keywords: Novel